Negotiating Sacred Space And Urban Legality In An Informal Settlement (Ethnographic Study In Katiasa Village, Harjamukti, Cirebon City) - Nurlaili Khikmawati; Lisya Zahrotul Wardha (UIN Siber Syekh Nurjati Cirebon, 2025)
Housing is one of the basic human needs, but there are still many people who do not have a decent place to live. This phenomenon reflects the gap in the fulfillment of basic needs, including in urban areas such as Cirebon City. This research aims to understand the subcultures formed in communities living in the cemetery area, including adaptation patterns and strategies developed in facing various life struggles. The research used a qualitative method with a rapid ethnographic approach, where researchers were directly involved through observation, interviews, and documentation for approximately six months at the research location, namely Kampung Katiasa, Harjamukti Village, Cirebon City. The results showed that the people in the Kampung Katiyasa area are the fifth generation to live in the Kemlaten Public Cemetery (TPU) area. The experience of living side by side with death gave birth to a new meaning to the concept of home and death itself. The community faces various struggles, such as inner struggles, land ownership conflicts, and difficulties in accessing the economy. To overcome this, they developed survival strategies, including not building new buildings, saving money to face the possibility of eviction, and avoiding activities in the cemetery area at certain times. These findings show that the people of Kampung Katiasa tend to use adaptive strategies in responding to social and economic conditions.